Influence of Fe3+ and F- ions on PbO2 process of electrosynthesis. - Thanh, Đinh Thị Mai (Vietnam Journal of Chemistry, 2012)
The electrodeposition of PbO2 on 304 stainless steel in the presence of F- and Fe3+, separately or together in the growth solution, is examined.The same electrodeposition kinetics is obeyed in the absence and in the presence of Fe3+ and F- in solution. Surface analysis by XRD and SEM of the Fe and F-doped PbO2 films does not reveal major changes compared to undoped samples. The oxygen over-potentiel on Fe-F-PbO2 electrode is higher which without Fe and F.